2019
DOI: 10.1016/j.nicl.2019.101757
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for impaired olfactory function and structural brain integrity in a disorder of ciliary function, Usher syndrome

Abstract: Diseases involving cilia dysfunction, such as Usher Syndrome (USH), often involve visual and auditory loss. Psychophysical evidence has suggested that this may also hold true for the peripheral olfactory domain. Here we aimed to go a step further by attempting to establish relations between the integrity of cortical structures and olfactory function in this condition. We investigated olfactory function for USH types 1 (USH1) and 2 (USH2). Bilateral olfactory bulb (OB) volume and olfactory sulcus (OS) depth wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although contradictory studies have been subsequently reported ( van Aarem et al, 1999 ), one study indicated cilia axoneme impairment in sperm as part of the Usher syndrome pathogenesis ( Hunter et al, 1986 ). Further evidence implicating Usher syndrome as a ciliopathy is the accelerated age-related olfactory decline reported among Usher patients ( Ramos et al, 2019 ; Ribeiro et al, 2016 ). Additionally, a recent study showed reduced ciliogenesis in USH2A patient-derived human dermal fibroblasts compared to a healthy control ( Samanta et al, 2019 ).…”
Section: Usherin Protein – Localization Interacting Partners and Functionsmentioning
confidence: 99%
“…Although contradictory studies have been subsequently reported ( van Aarem et al, 1999 ), one study indicated cilia axoneme impairment in sperm as part of the Usher syndrome pathogenesis ( Hunter et al, 1986 ). Further evidence implicating Usher syndrome as a ciliopathy is the accelerated age-related olfactory decline reported among Usher patients ( Ramos et al, 2019 ; Ribeiro et al, 2016 ). Additionally, a recent study showed reduced ciliogenesis in USH2A patient-derived human dermal fibroblasts compared to a healthy control ( Samanta et al, 2019 ).…”
Section: Usherin Protein – Localization Interacting Partners and Functionsmentioning
confidence: 99%
“…Moreover, psychophysical assessments have revealed a consistent olfactory loss in USH [ 50 ]. A study on brain structural integrity also found that the olfactory sulcus was shallower in USH patients compared to the control group [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover psychophysical assessment reveals consistent olfactory loss in USH (Ribeiro et al, 2016 ). A study on brain structural integrity also showed that the olfactory sulcus was shallower in USH patients when compared with the control group (Ramos et al, 2019 ). Studies in mice have also provided evidence for USH olfactory impairment (Jansen et al, 2016 ; Sahly et al, 1997 ; Wolfrum et al, 1998 ).…”
Section: Introductionmentioning
confidence: 96%